External Influence as an Indicator of Scholarly Importance - Ho Fai Chan; Bruno S. Frey; Jana Gallus; Markus Schaffner; Benno Torgler; Stephen Whyte (Center for Research in Economics, Management and the Arts (CREMA), 2014)
The external influence of scholarly activity has to date been measured primarily in terms of publications and citations, metrics that also dominate the promotion and grant processes. Yet the array of scholarly activities visible to the outside world are far more extensive and recently developed technologies allow broader and more accurate measurement of their influence on the wider societal discourse. Accordingly we analyze the relation between the internal and external influences of 723 top economics scholars using the number of pages indexed by Google and Bing as a measure of their external influence. Although the correlation between internal and external influence is low overall, it is highest among recipients of major key awards such as the Nobel Prize or John Bates Clark medal, and particularly strong for those ranked among the top 100 researchers.
Keywords: A11; A13; Z18; Z19; 330; academia; scholarly importance; role of economics; social importance of economists; external; internal influence; academic performance; awards